Communicative aspects and coping strategies in patients with Parkinson's disease - Flávia Pereira da Costa (Arquivos de Neuro-Psiquiatria)
Purpose: To investigate in patients with Parkinson's disease (PD), which are the coping strategies used and the relation between type of coping, voice symptoms and communicative aspects. Method: 73 subjects, 33 in the experimental group, with diagnosis of PD, and 40 subjects in the control group, healthy and without vocal complaints. They underwent the following procedures: application of the Voice Symptons Scale – VoiSS – Brazilian Version, Voice Disability Coping Questionnaire – VDCQ – Brazilian Version, and the questionnaire Living with Dysarthria – LwD. Results: The experimental group showed deviations in all protocols: VDCQ (p<0.001), VoiSS (p<0.001), LwD (p<0.001). The most frequently used coping strategy was self-control (p<0.001). The correlation between vocal symptoms and communicative aspects showed that the greater the impairment in communication, the greater the VoiSS emotional scores and the greater will be the amount of voice symptoms and signs. However, the vocal signs and symptoms and communicative aspects showed no correlation with coping. Conclusion: Patients with PD have a high amount of vocal signs and symptoms and the higher the occurrence, the more the patient reports being difficult to live with dysarthria, particularly when there are deviations in the emotional domain.